The challenge of organised crime to criminal proceedings - Weißer, Bettina (Organised crime, criminal procedure, and prisons, 2025)
This chapter provides an overview of the challenges posed by organised crime to criminal justice proceedings. Since the driving force behind such crimes is the organisation itself, it does not suffice to investigate individual crimes that have already been committed. Instead, law enforcement authorities must target the organisation itself in order to dismantle its business structures and thus effectively prevent it from initiating crimes in the future. After a brief description of the specific difficulties in combating organised crime, a variety of procedural countermeasures are presented.